Leadership Effectiveness: Education for Sustainable Development - Yusup, Muhammad; Dirga, Muhammad; Sholeh, Rifai Hasan (Development: Studies in Educational Management and Leadership, 2024)
This study explores the effectiveness of leadership in Education for Sustainable Development (ESD) amid growing environmental and social challenges that demand the integration of sustainability principles into the curriculum. Employing a qualitative approach through in-depth interviews and case studies at a number of institutions that have successfully implemented sustainable education practices, this study shows that effective leadership is characterized by the ability to inspire, educate, and empower the educational community. Successful leaders are able to build a shared vision and facilitate collaboration across stakeholders—students, teachers, and the community. The findings also emphasize the importance of leadership training that focuses on communication, problem-solving, and innovation skills to achieve ESD goals. Therefore, the effectiveness of leadership in ESD depends not only on formal policies but also on interpersonal skills and consistent commitment to the vision of sustainability. These findings provide practical insights for policymakers and education practitioners in designing more impactful leadership programs.